Matricellular Receptors as Potential Targets in Anti-Cancer Therapeutic Strategies - Herve Emonard (Frontiers Research Topics, 2016)
The invasive character of a primary cancer is greatly dependent on numerous interactions between tumor cells and their extracellular surroundings. Matricellular receptors are defined as (cell-surface) receptors that bind extracellular matrix (ECM) structural proteins and soluble factors dynamically acting on ECM homeostasis. Matricellular receptors mediate numerous signalings from the extracellular environment to cell nucleus and drive main biological functions that are cell growth, survival and migration. Numerous data from the last decade evidence that matricellular receptors are biosensors that allow to a tumor cell answering to microenvironmental variations, and in this sense they are important contributors to tumor cell malignancy. Matricellular receptors represent thus valuable targets for the development of original anti-cancer strategies. Original reports, bibliographic reviews or hypotheses are welcome to improve the basic knowledge of matricellular receptor properties, their spatio-temporal regulation, the dynamic formation of complex receptors and the impact of such interactions on the invasive properties of tumor cells. Biological, biophysical and pharmacological, as well as in silico contributions will be appreciated.